2003
DOI: 10.1093/humrep/deg479
|View full text |Cite
|
Sign up to set email alerts
|

Performance of five serological chlamydia antibody tests in subfertile women

Abstract: In screening for tubal factor subfertility, MIF Labsystems was superior to the ELISA tests evaluated, and combining two CAT tests did not improve its predictive value. Economic analysis will show whether serial testing by pELISA Medac, and retesting positive samples by MIF Labsystems, is most cost-effective. In CAT, cross-reactivity with C. pneumoniae antibodies is still a major concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 23 publications
6
66
0
2
Order By: Relevance
“…Thus far, few studies have compared these new serological assays with the MIF assay. The findings of our study are consistent with previous studies that revealed good sensitivities and specificities of ELISA assays based on peptides from the major outer membrane protein (MOMP) [15,17]. Paukku et al [18] compared the MIF assay to the ELISA Ani Labsystems for 78 patients with tubal factor infertility and showed a good correlation between the results of these assays.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus far, few studies have compared these new serological assays with the MIF assay. The findings of our study are consistent with previous studies that revealed good sensitivities and specificities of ELISA assays based on peptides from the major outer membrane protein (MOMP) [15,17]. Paukku et al [18] compared the MIF assay to the ELISA Ani Labsystems for 78 patients with tubal factor infertility and showed a good correlation between the results of these assays.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that CAT is more accurate in predicting distal tubal pathology, instead of unspecified tuboperitoneal abnormalities or proximal tubal occlusion [11]. Moreover, in studying the implications of different cutoff titres for a positive test, it has been noted that increasing the cutoff titre will improve the specificity, at the expense of sensitivity [7,12,15]. In patients with laparoscopically detected tubal pathology but negative antibody titres, diminished antibody titres related to time has been considered by some authors but not by others [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the chlamydial serological results were significantly associated with tubal infertility in the validation infertility clinic group (group 4). This result was inconsistent with most published studies, where chlamydial serology is typically significantly associated with tubal infertility (Akande et al, 2003;Mehanna et al, 1995;Claman et al, 1997;Land et al, 2003). However, it is possible that this is because the study included women with unknown tubal status in the comparison group, who would often be excluded in studies like this one.…”
Section: Discussionmentioning
confidence: 68%
“…In our study sensitivity for IgG Chlamydia trachomatis in adhesion and tubal obstruction was lower than in other studies. Land et al,( 2003) reports a Ig G antibodies for Chlamydia trachomatis sensitivity of about 60% for tubal pathology with a 85-90%specificity.…”
Section: Discussionmentioning
confidence: 99%